PEMERIKSAAN BORAKS PADA BAKSO YANG DIJUAL PEDAGANG KAKI LIMA DAN WARUNG BAKSO DI KELURAHAN PADANG BULAN KECAMATAN MEDAN BARU TAHUN 2014 - yustisia kesuma; devi nuraini santi; evi naria (Lingkungan dan Kesehatan Kerja, 2015)
Abstract There are many dangerous chemical substance that are not supposed to be added to food that are ended up added. This things happened because the merchants want his food to last longer, but he doesn’t have the knowledge of how to preserve food correctly, one of the example of this is the usage of borax in making meatballs. The purpose of this research is to know the amount of borax used in meatballs that are sold in Padang Bulan district of Medan Baru. The type of this research is descriptive survey through qualitative laboratorium check. This research was done on September – October 2014. The subject of this research is all of the food merchants who sold meatballs in dr. Mansur street in Padang Bulan district of Medan Baru that amounts to 25 merchants. The sample of this research is all of the subjects, which consist of 10 meatballs stalls and 15 street vendors. The received data is analized descriptively. Next, the research result are compared with Indonesia Minister of Health Rule Number 033 Year 2012 about Food Addition Substance. The results of this research showed that as many as 72% of merchants aged 20 – 39 years, 68% had an education level of primary school and high school/equivalent, 36% has been trading for 3 and 5 years, 60% had financial capital of Rp. 500.000 – Rp. 2.500.000, 56% level of knowledge street vendors and meatballs stalls in middle category. Results of laboratory tests showed that as many as 76% of the examined meatballs containing borax. Physically, meatballs containing borax is more supple, when bitten will return to forms initially, and durable. The author suggest to The Drug and Food Administration Board (BPOM) in Medan City are expected to conduct training, supervision, and periodic evaluation of the street vendors and meatballs stalls.